Culinary exploitation of nopal cactus pear in arid region - Saroj, P L; Singh, Dhurendra; Kumar, Kamlesh (Indian Horticulture, 2019)
In India, cacti were largely known as ornamental plants and find place either as component of rock garden or planted in pots in kitchen garden. Sometimes, thorny cactus plants are also planted along the field boundaries as live fences. It can also be seen growing in wild form in forest and wastelands. However, cactus as edible plant (fruits/ leaf pads) was largely ignored till recently by the scientific community but with increasing awareness about diversified usages and health promoting benefits; some organizations started collection and evaluation of cactus pear in India. Moreover, it has not gained momentum due to its inherent constraints like thorny nature, low fruit yield and poor shelf life of fruits. At Central Institute for Arid Horticulture, Bikaner, we have selected a cactus clone of nopales group having thorn less cladodes (leaf pads) at tender stage and can be utilized for delicious culinary preparations like vegetable, salad and pickles; while fruits for preparation of attractive pink colour syrup as well as extraction of natural colorant used in food and dairy industries. This clone can be cultivated in tropical and semi-arid regions as rainfed and in hot arid region under limited irrigation with caution that it should be protected from animals and wild life as its cladodes are very tasty.